Characterization of Rickettsia raoultii replication kinetics in different tick cell lines / Nurul Aini Husin - Nurul Aini , Husin (2022)
Rickettsia raoultii is a spotted fever group rickettsia and emerging pathogen that poses a threat to public health with Dermacentor species of ticks as the main vector and known as one of the causative agents of tick-borne lymphadenopathy (TIBOLA) in humans. This bacterium was previously isolated into and propagated in tick and mammalian cell lines. Although the growth characteristics of R. raoultii have been investigated in mammalian cells, the same has not been investigated in detail in tick cells. In this study, the growth and replication kinetics of R. raoultii in three tick cell lines derived from different tick genera, Rhipicephalus microplus-derived BME / CTVM23, Rhipicephalus sanguineus-derived RSE / PILS35 and Ixodes scapularis-derived IDE8 tick cell lines were presented. Tick cell cultures were infected in duplicate with cryopreserved R. raoultii prepared from the homologous cell lines. In all infected cell cultures, 100 % of the cells were infected by 12 to 14 days post infection as visualized in Giemsa-stained cytocentrifuge smears. A rickettsiae-specific citrate synthase (gltA) gene quantitative polymerase chain reaction (qPCR) assay was used to demonstrate the replication kinetics of R. raoultii in the infected cultures. The R. raoultii growth curves were exhibited with initial lag, exponential, stationary and death phases. Exponential phases between 4 and 12 days and generation times between 0.9 and 2.6 days were observed in the R. raoultii-infected tick cell cultures. The highest levels of multiplication of R. raoultii in BME / CTVM23 and RSE / PILS35 cultures were, respectively, 39.5 and 37.1-fold increases compared to the inoculum. In contrast, the highest level of multiplication of R. raoultii in IDE8 cultures was 110.1-fold greater than the inoculum. In addition, a 7 day stationary phase was observed in R. raoultii-infected IDE8 cultures. The findings here suggest that there is variation in the growth kinetics of R. raoultii in the different tick cell lines tested, amongst which IDE8 cells could tolerate the highest levels of R. raoultii replication. Variations in genotypic and phenotypic characteristics, as well as species differences between tick cell lines, may have contributed to this finding. Further studies into the characterization of R. raoultii and its interaction with tick vectors are needed to better understand its survival within tick populations, and tick cell lines remain an important tool to this end.